Women and wrongful convictions: concepts and challenges - Parkes, Debra; Cunliffe, Emma (International Journal of Law in Context, 2015)
This paper draws from the wrongful convictions of women to interrogate the limits of dominant conceptions of wrongful conviction. Most North American innocence projects turn on a conception of demonstrable factual innocence. The paper argues that this focus is problematic as a matter of criminal law principle and presents particular difficulties for women. The paper identifies that family violence forms the primary context for both the conviction of women for violent crimes, and for women's wrongful convictions. Taking two key examples of family violence – child homicide and intimate partner violence – we illustrate that the prevailing focus on demonstrable factual innocence fits awkwardly with identified wrongful convictions in these areas, and argue that this focus may deflect attention from unidentified miscarriages of justice. We suggest that focusing on factual innocence undermines the criminal justice system's proper focus on state responsibilities, including the responsibility to protect women and children from harm, and the asymmetric burden of proof that applies in criminal cases.